Analysis of Service Quality at Islamic Banks in Bengkulu City (Study at BSI Bank KC S. Parman 1) - Anugrah Mahesa, Khodijah; Isnaini, Desi; Pahrudin, (Sharia Economic and Management Business Journal (SEMBJ), 2025)
The aim of this research is to determine the service quality of Bank Syariah Indonesia KC S. Parman 1 Bengkulu. This research is field research using a descriptive qualitative approach. The data sources used in this research are primary data and secondary data. The data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this research indicate that the services at the Indonesian sharia bank KC S. Parman 1 Bengkulu provide services for customers. This is demonstrated through 5 (five) factor dimensions, namely: tangible (physical evidence), Reability (reliability), Responsiveness (responsiveness), Assurance (guarantee) and Empaty (empathy). The results of this research indicate that the service quality of Bank BSI KC S. Parman 1 is quite satisfactory for customers. However, there are still several factors that can be improved, such as the mobile banking network which often has problems and the lack of ATM machine support. On the other hand, Bank BSI KC S. Parman 1 has carried out improvements and improvements to the facilities and services provided to customers every year.